The DnaJ-Hsp70-Hsp90 co-chaperon networks in scallops under toxic Alexandrium dinoflagellates exposure - Moli Li; Jie Cheng; Huizhen Wang; Jiaoxia Shi; Xiaogang Xun; Wei Lu; Xubo Wang; Jingjie Hu; Zhenmin Bao; Xiaoli Hu (Ecotoxicology and Environmental Safety)
Heat shock proteins (Hsps) are highly conserved molecular chaperones with essential roles against biotic and abiotic stressors. A large set of co-chaperons comprising J-domain proteins (DnaJs) regulate the ATPase cycle of Hsp70s with Hsp90s, together constituting a dynamic and functionally versatile network for protein folding/unfolding and regulation. Marine bivalves could accumulate and tolerate paralytic shellfish toxins (PSTs), the well-noted neurotoxins generated during harmful algal blooms. Here, 37 CfDnaJ and 35 PyDnaJ genes were systematically characterized in Zhikong scallop (Chlamys farreri) and Yesso scallop (Patinopecten yessoensis), the important aquaculture bivalve species in China. After exposure to different PST-producing dinoflagellates, Alexandrium minutum and Alexandrium catenella, diverse DnaJ regulations were presented in scallop hepatopancreas, accumulating incoming PSTs, and kidneys, transforming PSTs into higher toxic analogs. CfDnaJs’ up-regulation in kidneys was similar with that in hepatopancreas, while their down-regulation was stronger in kidneys than in hepatopancreas, with CFA.38965.19.DNAJC30 being continuously down-regulated in both tissues of the two algae exposure. Moreover, PyDnaJs’ up-regulation was only found in kidneys after A. catenella exposure, and PYE.10799.6.DNAJB1 was down-regulated in both tissues through the experiment. Together with the expression trends and correlation of DnaJ-Hsp70-Hsp90 genes, the organ-, toxin-, and species-dependent Hsp70B2 expressions were coordinately co-expressed with diverse DnaJ members, suggesting the functional diversity of scallop DnaJs with conserved Hsp70B2s in response to stress by PST-producing algae. Our results confirmed the regulated coordination of DnaJ-Hsp70B2 co-chaperons in scallops, and provided vital insights into the function and adaptation of scallop Hsps in response to PST stress.